Increased Resisted Sprinting Load Decreases Bilateral Asymmetry in Sprinting Kinetics Among Rugby Players. Issue 11 (November 2021) - Mangine, Gerald T.; McNabb, Jacob A.; Feito, Yuri; VanDusseldorp, Trisha A.; Hester, Garrett M.
Abstract : Abstract: Mangine, GT, McNabb, JA, Feito, Y, VanDusseldorp, TA, and Hester, GM. Increased resisted sprinting load decreases bilateral asymmetry in sprinting kinetics among rugby players. J Strength Cond Res 35(11): 3076–3083, 2021—To examine the effect of resistance on sprinting kinetics and their bilateral symmetry, 15 male collegiate rugby players completed 3 maximal, 40-m sprints (S1–S3) while tethered to a robotic resistance device. Minimal resistance (9.81 N) was used on S1 (familiarization) and S2, while S3 was loaded at 147.1 N. Peak and average (AVG) power (P), velocity (V), force (F), and rate of force development (RFD) were averaged within the first stride, the acceleration and peak velocity phases, as well as across the 40-m sprint. Bilateral percent differences were calculated from step values within each stride for each variable. Friedman's rank tests revealed differences ( p ⩽ 0.02) between sprint trials and phases for each variable. During both trials, most kinetic measures increased from the first stride through the peak velocity phase ( p ⩽ 0.036), although reductions in RFDPEAK ( p ⩽ 0.015) and RFDAVG (S3 only; p < 0.001) were observed within the peak velocity phase. Comparatively, sprinting velocity and average stride (length and duration) were less during S3, while all other measures were greater within each phase. Across the entire 40-m sprint, S3 reduced ( p < 0.05) asymmetry for average stride length (−2.1 to −17.0%), VPEAK (−0.8 to −4.9%), VAVG (−2.3 to −6.0%), FPEAK (−5.6 to −8.7%), FAVG (−3.4 to −7.1%), RFDPEAK (−4.3 to −36.7%), PPEAK (−5.9 to −12.4%), and PAVG (−5.4 to −9.8%). Applying sprinting resistance may be a tool for reducing acute bilateral asymmetries in sprinting kinetic measures.